The Impact of Global Warming on Silicon PV Energy Yield in 2100 - Peters, Ian Marius; Buonassisi, Tonio (Conference Record of the IEEE Photovoltaic Specialists Conference, 2019)
While the installed photovoltaic (PV) capacity grows to a terawatt scale, effects of global climate change unfold. The question arises, how a changing climate, and especially raising temperatures, will affect the performance of PV installations in the future. In this paper we present an estimate of the reduction in energy yield for silicon PV installations due to global warming in the year 2100. Using IPCC global warming scenarios and published temperature coefficients for today's silicon PV panels, we project median reductions in annual energy output of l5kWh/kWp, with reductions up to 50kWh/kWp in some areas. Higher efficiency cells and advanced cell and module architectures can significantly reduce these losses.
CRIS-Team Scopus Importer:2022-06-05